2004
DOI: 10.1111/j.0030-1299.2005.13609.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual size dimorphism within species increases with body size in insects

Abstract: Teder, T. and Tammaru, T. 2005. Sexual size dimorphism within species increases with body size in insects. Á/ Oikos 108: 321 Á/334. Studies examining interspecific differences in sexual size dimorphism (SSD) typically assume that the degree of sexual differences in body size is invariable within species. This work was conducted to assess validity of this assumption. As a result of a systematic literature survey, datasets for 158 insect species were retrieved. Each dataset contained adult or pupal weights of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

37
283
4
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 300 publications
(326 citation statements)
references
References 162 publications
37
283
4
2
Order By: Relevance
“…This is equivalent to a pattern of (phylo)genetic variation in male body size being generally greater than that of females (Blanckenhorn et al, 2007b). In contrast, our results here rather agree with opposite patterns of phenotypic variance found in insects (Teder and Tammaru, 2005). Blanckenhorn et al (2007b) also found incongruent SSD patterns among species (according to Rensch's rule) vs among populations and among families within species (inconsistent with Rensch's rule) for sepsid flies with female-biased SSD, but not for scathophagid flies with male-biased SSD.…”
Section: Discussionsupporting
confidence: 82%
“…This is equivalent to a pattern of (phylo)genetic variation in male body size being generally greater than that of females (Blanckenhorn et al, 2007b). In contrast, our results here rather agree with opposite patterns of phenotypic variance found in insects (Teder and Tammaru, 2005). Blanckenhorn et al (2007b) also found incongruent SSD patterns among species (according to Rensch's rule) vs among populations and among families within species (inconsistent with Rensch's rule) for sepsid flies with female-biased SSD, but not for scathophagid flies with male-biased SSD.…”
Section: Discussionsupporting
confidence: 82%
“…This might also be a contributing factor to the male biased sex ratio that is often found in small populations before the extinction of that population (see Gabriel and Ferriere, 2004). It is known that females are more sensitive to environmental stress than males (Teder and Tammaru, 2005): the results of the present study suggest that part of this sensitivity is genetically based.…”
Section: Discussionmentioning
confidence: 52%
“…Rensch's rule (RR) states that male body size varies more than female body size, irrespective of which sex is larger. RR was originally formulated to describe the pattern seen across species within a related clade, but has since been tested within species to see if similar drivers exist at the intra-specific level [13,17]. Within a species, it predicts an increase in SSD with increasing body size in species where males are the larger sex, and a decrease in SSD with body size in species where females are larger [14,16].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we specifically focus on sex-dependent differences in T-S responses, as this may ultimately help to elucidate the underlying drivers of both SSD and T-S responses. Sex-based differences in T-S responses have been considered before; while most studies have been experimental and have considered single species, the syntheses and analyses of responses by Teder & Tammaru [13] and Stillwell et al [19] on insects, have looked more broadly at differential changes in SSD with environmental conditions. We increase the amount of temperature response data considered by almost fourfold in our analysis and increase the range of species to include other Arthropoda.…”
Section: Introductionmentioning
confidence: 99%